Kemampuan representasi matematis siswa: Systematic literature review - Noor Annisah Sholehah; Kartika Yulianti; M Akbar Gulvara; Surya Kurniawan; Nur Rofi'ah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to describe students' mathematical representation abilities in terms of self-efficacy and cognitive style. Systematic Literature Review (SLR) is the method used in this research. The population in this study is all primary studies regarding students' mathematical representation abilities, and the sample is primary studies located in Indonesia, from 2013 to 2022, found on ERIC or Google Scholar. The research sample consisted of 31 articles consisting of 13 articles based on self-efficacy and 18 articles based on cognitive style. The conclusion is that from 2016 to 2022, every year, there are publications regarding mathematical representations, and they are dominated at the junior high school. The dominant research was conducted in the Java area, geometry is a mathematic topic that has been researched the most, and the results of this research have been published in SINTA the most. In general, mathematical representation ability is directly proportional to self-efficacy. Witkin & Goodenough theory is dominantly used in cognitive style.